Dengue - should we look for confirmation? - Srigade, Vedavyasa; Bingi, Koteshwar (Indian Journal of Child Health, 2016)
Background: Children are at great risk of dengue infection and mortality. Pediatric dengue management needs early identification and timely intervention. Objective: Evidence for case management based on clinical diagnosis without waiting for confirmation is aimed at in this study. Methods: Retrospective medical record review of pediatric clinical and confirmed dengue cases was done. Children admitted during 6 months in 2015 at Institute of Child Health, Niloufer Hospital, Hyderabad, were included in the study. 3 demographic, 32 symptom, 24 sign, and 24 investigation data were collected. Proportions of individual findings of the total number of patients in the group were compared between clinical and confirmed dengue groups. Results: Of the 13,750 admissions, 282 serologically confirmed dengue cases, 407 clinical dengue cases, 4 confirmed dengue deaths, and 24 clinical dengue deaths, making a total of 717 patient data were analyzed. Case fatality rate was 4.06% (95% confidence interval: 2.56-5.57). Except 9 out of 83 parameters, no significant differences of proportions between the groups were present. Age